Sociodemographic, dietary pattern, serum biomarkers (insulin-like growth factor 1 (igf-1) and insulin-like growth factor binding protein 3 (igfbp-3)) and genetic polymorphisms in breast cancer among palestinian women: a case control study - Arafat, Heba M. J. (2025)
Breast cancer (BC) remains a global public health challenge. This case-control study explores the relationships between serum insulin-like growth factor binding protein 3 (IGFBP-3), insulin-like growth factor 1 (IGF-1), genetic polymorphisms, dietary patterns, and BC risk in Palestinian women. The study involved 112 newly diagnosed BC confirmed by histopathology and 222 age-matched, cancer-free controls. Data collection included face-to-face interviews, biochemical, genetic, and immunohistochemical analyses, and bioinformatics. Tumour tissue samples from BC cases were analysed for ER, PR, and HER-2 status. SPSS program version 28 was used for all data analysis. Multivariate analysis revealed that elevated serum IGF-1 levels were associated with increased BC risk (OR=1.013; 95%CI 1.007, 1.019), as well as ER(+)/PR(+) status (rs= 0.232, p ≤ 0.001) and advanced disease stages (III and IV) (rs= 0.191, p ≤ 0.001; rs= 0.119, p = 0.029) respectively. Higher BC odds were linked to never being pregnant (OR=2.122; 95%CI 1.022, 4.408), first delivery at ≤18 years (OR=6.033; 95%CI 2.217, 16.413), and low-intensity exercise (OR=9.609; 95%CI 1.009, 91.471). Conversely, women aged 35–40 years had a reduced BC risk compared to those <35 years (OR=0.427; 95%CI 0.188, 0.971). The IGFBP-3 A-202C polymorphism showed significant associations with BC risk. The homozygous CC allele was more frequent in cases (70.5%) compared to controls (20.7%) and linked to elevated IGFBP-3 (rs = 0.164; p = 0.003) and IGF-1 levels (rs = 0.175; p ≤ 0.001), and an increased risk of BC (OR=16.237; 95%CI 7.904, 33.356, p ≤ 0.001). Moreover, the IGFBP-3 A-202C genotype was significantly associated with PR status and double positive hormone receptor ER/PR (p = 0.020). Furthermore, bioinformatics analysis identified IGF-1 variants (rs1520220, rs6214, rs7136446, rs6220) significantly associated with breast carcinoma and malignant neoplasm of the breast (p-value = 6.29E−0.6 and 2.84E−0.6) respectively. Additionally, the dietary analysis revealed that eight of the 14 food groups studied were linked to a decreased risk of BC, including fresh fruits and their juices (OR= 0.966; 95%CI 0.947, 0.985), meat products (OR= 0.963; 95%CI 0.934, 0.993), grains (OR=0.944; 95%CI 0.912, 0.977), low-fat dairy (OR=0.970; 95%CI 0.945, 0.995), nuts (OR=0.835; 95%CI 0.745, 0.936), snacks and sweets (OR=0.967, 95%CI 0.937, 0.998), and soups and sauces (OR=0.945; 95%CI 0.911, 0.979), were associated with a reduction in BC risk, while eggs were associated with increased risk (OR=1.125; 95%CI 1.019,1.243) with p-values < 0.05. Drinks and beverages was positively correlated with IGF-1 levels (rp = 0.121, p = 0.027). These findings underscore the importance of IGF-1 and IGFBP-3 as potential biomarkers for BC risk. Integrating genetic, biochemical, dietary, and lifestyle factors provides novel insights for personalized prevention and treatment strategies, particularly in resource-limited settings such as the Gaza Strip